Nonepileptic seizure: paroxysmal events of psychogenic origin - Gamba da Silva, Gabriela; Cristina Pontarolo Lidoino, Andreia (Seven Editora, 2023)
This article deals with non-epileptic seizures in paroxysmal events of psychogenic origin. It discusses the difficulties that health professionals, responsible for diagnosis, have when dealing with individuals who present epileptic signs and symptoms, but which are not related to epilepsy. In this context, the general aim is to investigate how the process of diagnosis of non-epileptic Psychogenic Crisis (PNES) takes place. To this end, the methodological procedure reported the use of bibliographic research through data collection of published articles that cover and portray the theme directed to clinical practice, thus, academic publications were analyzed, selected those of interest, and through observation, the data were analyzed to gather the knowledge produced on the subject. After the research, it was concluded that health teams must know the characteristics, diagnosis, and treatment of a PNES so that when facing any apparent occurrence, the individual’s life history is investigated in detail and the individual is referred to video-electroencephalography to correctly rule out or confirm the investigation and offer a resolutive treatment. DOI: 10.56238/pacfdnsv1-076